Individual biovolume of some dominant copepod species in coastal waters off Buenos Aires Province, Argentine Sea - Viñas, Maria Delia (2010)
Copepods are key components in the marine communities because of their important role in the transfer of matter and energy from primary producers to higher trophic levels and in the export of organic matter from the euphotic to deeper layers of the oceans (CALBET et al., 2000). Because of their role as prey for fishes at different stages of development, knowledge of zooplankton abundance and biomass in spatial and temporal scales remains a key element of the marine ecosystem approaches (IRIGOIEN et al., 2009).